Negative resistance characterisation and defective trap exploration in ZnO nonvolatile memory devices. (17th March 2014) - Chiu, Fu-Chien; Huang, Chih-Yao; Chang, Wen-Yuan; Pan, Tung-Ming
In this work, Pt/ZnO/Pt capacitors were fabricated and investigated for nonvolatile memory applications. The memory devices exhibit bipolar resistance switching characteristics. Using a current-bias method, a negative resistance or snapback characteristic is observed when the memory device switches from a high-resistance state to a low-resistance state owing to the formation of filamentary conducting path. With DC cycling endurance tests, the more set/reset switching cycles are performed, the more times of snapbacks are found. The multiple snapbacks are associated with the additional conducting filaments formed nearby the original filament. By the explorations of temperature-dependent current-voltage characteristics and X-ray photoelectron spectroscopy spectra, the filaments may be related to the defect state of interstitial zinc with the trap spacing of 2 nm and the trap energy level of 0.46 eV in ZnO films.